Prediction of lipohypertrophy in patients with diabetes mellitus - V Brijeetha; Jonita Evett Fernandes; Jyothi Idiculla (Wolters Kluwer Medknow Publications, 2020)
Introduction: Lipohypertrophy (LH) may result in variable absorption of insulin and affect glycemic control. Objectives: This study aimed to study the risk factors and prevalence of lipohypertrophy in diabetic patients at a tertiary hospital in South India. Methodology: 206 patients with diabetes mellitus aged over 18 years of age, on insulin therapy for over two years, were included in this study conducted at St Johns Medical Hospital to explore the prevalence and risk factors for development of lipohypertrophy. Demographics, duration of diabetes and insulin therapy, type of needles used, times of reuse, injection technique was recorded. The injection sites were inspected meticulously for the presence of lipohypertrophy. Results: 66 patients (32%) were found to have LH of which 62 had Type 2 diabetes and 4 had Type 1 diabetes. The median duration of diabetes was 15 years (IQR 10-20) and was higher in the group with LH (P=0.000). The duration of insulin therapy was 10 years (IQR 5-10.5) and was significantly higher in the group with LH (P=0.000). The commonest site for insulin injection was the abdomen and it was associated with LH (P=0.000).Patients reusing the needles over 6 times and those who failed to rotate injection sites had the highest frequency of LH(P=0.000). Conclusions: Patients on long term insulin should be advised against the reuse of needles to save on cost of therapy in view of increased risk of LH and glycemic variability. Physicians must reinforce proper insulin injection technique periodically and document lipohypertrophy if present.